Indigenous Perspective of Lymphatic Filariasis in Endemic Region Indonesia - Mara Ipa; Endang Puji Astuti; Bina Ikawati; Tri Wijayanti; Yulidar Yulidar; Nur Ramadhan; Made Agus Nurdjana; Nita Rahayu; Rais Yunarko; Agung Dwilaksono (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
Lymphatic filariasis disease impacts the patients both socially and economically. Health seeking behavior was related to the variation of local perceived. This research is required to explore the wide variety of local perspectives as input into treatment program intervention strategies. The study was conducted in 12 districts in Indonesia, namely Pidie, North Aceh, Aceh Jaya, West Pasaman, South Pesisir, Subang, Tangerang, West Kota Waringin, North Hulu Sungai, Donggala, Bombana, and Asmat. Qualitative methods with the health belief model approach were used to assess the community’s knowledge about lymphatic filariasis disease and its treatments. This study used 24 informants consisting of 14 men and 10 women. Results showed there were 9 out of 12 regions that have a localized concept of lymphatic filariasis disease. Most informants believe that the disease occured as a result of the curse of the ancestor or the curse of visiting a certain place, or supernatural power. Most informants stated that seeking indigenous healers was carried out if the informant felt that self-treatment did not produce the result as expected. There was a tendency between knowledge and elimination efforts of lymphatic filariasis disease. Therefore, it is recommended to provide a better understanding of local knowledge about lymphatic filariasis